(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Excess water content within the building material could greatly alter the interaction of the microwave with the material. In this study aerated concrete (AEROC) block walls (60x60cm) were investigated for their microwave (2.4 GHz) properties under wetting conditions. The spray wetting of the wall was conducted to simulate the environmental processes such as raining or water damage. 50ml/m² water dosage was applied on the surface of the concrete 21 times in 1 min intervals. The results show a noticeable decrease in microwave penetration power through the material after the sample gets enriched with water. As the water content on the surface of the material rises, so does the transmission loss. During the different water content of the aerated concrete, the reflection loss varied from -15.04 dB (dry wall) to -5.03 dB (wet wall’s surface). The transmission loss continues to rise during the entire length of the experiment, from -4.5 dB as a dry sample to -8.3 dB after 441 ml (1035 ml/m² during 23 min) of sprayed water. The variation of reflected microwave power was approximately ten times, which is quite a significant indicator of alteration of microwave propagation. The results demonstrate wetting process as an considerable factor in assessing microwave propagation in near the sources, such as mobile phone base station antennas, industrial microwave heaters and ovens etc.